2010
DOI: 10.1002/jmv.21869
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of antibodies to swine influenza viruses in humans with occupational exposure to pigs, Thuringia, Germany, 2008–2009

Abstract: The Eurasian lineages of swine influenza viruses are different genetically from classical swine H1N1 influenza viruses and comprise avian-like H1N1 and human-like H1N2 and H3N2 subtypes. Although sporadic isolation of such viruses from human specimens has been reported, the prevalence of human infections is not known. In the present study, the seroprevalence against Eurasian swine influenza viruses was investigated. Sera were collected in Thuringia, Germany, from December 2007 to April 2009. The study group co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 20 publications
2
21
0
Order By: Relevance
“…The control group consisted of 116 Thuringian blood donors without pig contact which were frequency matched by gender and age (39 years and below, 40-49 years, and 50 years and above). This is in accordance with our previous publication [18]. The study group comprised of 45 women (42.5%) and 61 men (57.5%).…”
Section: Methodssupporting
confidence: 91%
See 2 more Smart Citations
“…The control group consisted of 116 Thuringian blood donors without pig contact which were frequency matched by gender and age (39 years and below, 40-49 years, and 50 years and above). This is in accordance with our previous publication [18]. The study group comprised of 45 women (42.5%) and 61 men (57.5%).…”
Section: Methodssupporting
confidence: 91%
“…However, for Germany, such data are currently not available. Therefore, we used a well-characterised set of sera which were initially collected to analyse the risk of zoonotic influenza A virus infection [18]. Some of these samples had to be excluded from the present setting since not enough material was available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were propagated in Eagle's minimum essential medium (EMEM) supplemented with 10% (v/v) fetal bovine serum, 100 U/ml penicillin, 100 g/ml streptomycin and 2 mM L-glutamine. The HI assay was conducted in large accordance to the WHO protocol and according to a study published previously [20]. BrieXy, serum samples were pretreated with (1) neuraminidase (Sigma N-3,001, Taufkirchen, Germany) 1:40 diluted with 0.9% (w/v) sodium chloride for 14-18 hours at 37°C.…”
Section: Hemagglutination Inhibition Assaymentioning
confidence: 99%
“…The reported seroprevalences differed greatly among studies. In populations occupationally exposed to swine, the prevalence of antibodies to H1N1v ranged from 0% to almost 80% [82,85], to H1N2v from 4% to 67% [72,82] and to H3N2v from 9% to almost 80% [49,72]. Looking only at the high quality studies (grades A or B), the reported prevalences were similar to those for C and D studies, with the exception of H3N2v, for which the highest reported seroprevalence was 28% [74] (Figure 4).…”
Section: Resultsmentioning
confidence: 99%